Tatar primer Atagaji/Iman Sharty as an object of cultural heritage - Anfisa Nikolaevna Ibragimova, Alla Arkad’evna Salnikova, Dilyara Magzumovna Galiullina, (Opción, 2019)
The study aims to investigate Tatar Primer Atagaji / Iman Sharty as an object of cultural heritage via the reconstruction of the history of creation and existence of a text in culture and the analysis of the Atagaji primer. As a result, the primer as a socio-cultural phenomenon and an important object of cultural heritage today attracts the increased attention of scientists. In conclusion, the Tatar Primer Atagaji / Iman Sharty is considered not only a national educational book of elementary literacy but also an important tool of cultural and educational policy.